Virtual look around: suitability evaluation for virtual tour in multiple platforms - Rodrigues, Adriel; Cheiran, Jean Felipe Patikowski (Anais do Simpósio de Realidade Virtual e Aumentada (SVR), 2020)
In the last few years, Virtual Reality (VR) has become easily available through different devices, from desktop to head-mounted displays (HMD). Virtual tour experiences, for instance, became popular by 360º panoramic photographs and video clips on online social media, so people could visit a remote location without being exposed to crowded transportation or places. Also, a virtual tour demonstrates considerable potential as a tool for escapism and even remote teaching in the current pandemic situation. However, we lack studies that evaluate the interaction quality in such virtual tours in different immersion levels. Since this kind of research is important to allow users to better balance cost-benefit decisions, the present paper aims to compare the interaction quality in a virtual tour website developed in WebXR through different devices. In order to achieve our objective, we developed a virtual tour based on 360º pictures using WebXR and React 360 and carried out a user study with 41 undergraduate students using four different devices: a laptop computer, a smartphone, a Google Cardboard headset, and a Samsung GearVR HMD. We evaluated users' attitudes by an adaptation of the Suitability Evaluation Questionnaire (SEQ), and users' performance by measuring time to fulfill a set of tasks. The key findings from our research include that (i) the overall self-reported experience using Google Cardboard is worse than using other devices, (ii) the users' performance is quite similar between the devices, and (iii) there is evidence of unexpected cybersickness symptoms in tests with the smartphone.